TANGGUNGJAWAB ADVOKAT DALAM PENEGAKAN HUKUM TERKAIT KESALAHAN PENGAJUAN TERHADAP KUMULASI GUGATAN DI PERSIDANGAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI NOMOR 687/PDT.G/2018/PN.JKT.UTR DAN 373/PDT.G/2018/PN.JKT.BRT) - Athalia Christine Lamretta Boru Simbolon; Ning Adiasih (Jurnal Hukum Adigama, 2020)
Responsibility is an act of self-awareness of every human being towards all behaviors and actions that are done intentionally or unintentionally. Responsibility also applies to every Advocate in operating their noble profession. However, in reality, not a few people who work in the advocate profession are often unable to uphold the ideals of the profession itself. In practice, in a court of law, there are not a few clients who suffer losses due to the inaccuracy of advocates used by these clients. As in the cumulative law case filed there is a case which judge opinion considered as a vague suit so that it was declared unacceptable. The failure of the advocate in handling a case may occur due to several reasons, namely because the advocate does not have good qualifications to handle cases in the field of law or the advocate does not have a good track record in advocacy, including concerning ethics, morals and honesty. Based on research that has been done, it can be concluded that advocates in law enforcement are responsible to God, to the Ethics Code, to the Law, and to the Community. The provisions on the application of the cumulative lawsuit at the trial have a close relationship, there is a legal relationship and the compatibility between Posita and Petitum. It is expected that every litigate party can be more careful in submitting legal remedie.